Improving learning in a professional context [ a research perspective on the new teacher in school - Blake, Allan; McNally, Jim (Improving learning TLRP., 2010)
Based on empirical research, including interviews with new teachers, by teachers themselves, this book reveals the complexity of learning in a professional context and gives some basic truths about